Long‐term outcomes of simultaneous heart and kidney transplantation in pediatric recipients. (20th July 2017) - Weng, Patricia L.; Alejos, Juan Carlos; Halnon, Nancy; Zhang, Qiuheng; Reed, Elaine F.; Tsai Chambers, Eileen
Abstract: Pediatric sHKTx has become an effective therapy for patients with combined cardiac and renal failure. Often, these patients develop human leukocyte antigen antibodies from their previous allografts and are therefore more difficult to re‐transplant. We describe the largest case series of a predominantly sensitized pediatric sHKTx with emphasis on medical management and patient outcomes. Demographics, clinical characteristics, antibody, and biopsy data were retrospectively collected from University of California, Los Angeles database and correlated with short‐ and long‐term patient and allograft outcomes of all sHKTx performed between 2002 and 2015. We identified seven pediatric patients who underwent sHKTx at our center. Mean age at time of sHKTx was 13.7 years and 85.7% were re‐graft patients. 57.1% were sensitized with cPRA >50% and another 57.1% had preformed donor‐specific antibody. Five‐year renal allograft survival and patient survival was 85.7% for both end‐points. The remaining six patients are all alive (mean follow‐up 78.5 months) with good kidney and heart function. sHKTx in a population with increased immunological risk can be associated with good long‐term outcomes and offers potential guidance to the pediatric transplant community where data are limited.